Geotechnical frontiers 2017. selected papers from sessions of Geotechnical Frontiers 2017, March 12-15, 2017, Orlando, Florida - Brandon, Thomas L.; Valentine, Richard J. (American Society of Civil Engineers, 2017)
Selected papers from Geotechnical Frontiers 2017, held in Orlando, Florida, March 12-15, 2017. Sponsored by the Industrial Fabrics Association International and the Geo-Institute of ASCE. This Geotechnical Special Publication contains 40 peer-reviewed papers on seismic performance and liquefaction. Topics include: seismic parameters and modeling; soil liquefaction; and numerical modeling for soil liquefaction. GSP 281 will be of interest to geotechnical engineers and researchers working in earthquake engineering.
Keywords: Geotechnical engineering -- Congresses.; Earthquake engineering -- Congresses.; Soil liquefaction -- Congresses.; Soil-structure interaction -- Congresses.; elektronické knihy; electronic books